2015
DOI: 10.1088/0964-1726/24/5/055015
|View full text |Cite
|
Sign up to set email alerts
|

An electromagnetic inerter-based vibration suppression device

Abstract: This paper describes how an inerter-based device for structural vibration suppression can be realized using an electromagnetic transducer such as a linear motor. When the motor shaft moves, a difference of voltage is generated across the transducer coil. The voltage difference is proportional to the relative velocity between its two terminals. The electromagnetic transducer will exert a force proportional to current following the Lorentz principle if the circuit is closed around the transducer coil. If an elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 29 publications
(53 reference statements)
0
58
0
Order By: Relevance
“…Compared with the performance of the TMD, the RIDTMD provides not only lower peak structural responses but also a wider suppression band with no increase in block strokes. In contrast, based on the force‐current electric‐mechanical analogy, Gonzalezbuelga et al proposed a device called an electromagnetic TID, which consists of a linear motor and an electric resonant circuit. The proposed electromagnetic TID is the equivalent system of the TID in electrical systems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the performance of the TMD, the RIDTMD provides not only lower peak structural responses but also a wider suppression band with no increase in block strokes. In contrast, based on the force‐current electric‐mechanical analogy, Gonzalezbuelga et al proposed a device called an electromagnetic TID, which consists of a linear motor and an electric resonant circuit. The proposed electromagnetic TID is the equivalent system of the TID in electrical systems .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, based on the force‐current electric‐mechanical analogy, Gonzalezbuelga et al proposed a device called an electromagnetic TID, which consists of a linear motor and an electric resonant circuit. The proposed electromagnetic TID is the equivalent system of the TID in electrical systems . In addition to the fixed‐inerter‐based TMD mentioned above, Mohammadi‐Ghazi et al proposed an adaptive‐configuration TMD consisting of fixed and moving parts.…”
Section: Introductionmentioning
confidence: 99%
“…An appealing property of inerters is that they can be designed and realized in practice having their inertance significantly larger than their mass [1,2]. This opens many interesting possibilities so that many authors reported on how to design and use inerters to suppress mechanical vibrations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, an electromagnetic transducer (voice coil, linear motor) can be shunted with electrical impedance. If the total shunt impedance is properly tuned, then the whole electromechanical network theoretically behaves exactly as if it incorporated an ideal inerter mounted in series with a parallel spring damper-pair [3]. In this context, self-powered configurations employing a simultaneous active control and energy harvesting have been considered to synthesize mechatronic inerters [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation